Functional characterization of thioredoxin 3 (TRX-3), a Caenorhabditis elegans intestine-specific thioredoxin - Jiménez-Hidalgo, María (Elsevier Science, 2014)
Thioredoxins are a class of evolutionarily conserved proteins that have been demonstrated to play a key role in many cellular processes involving redox reactions. We report here the genetic and biochemical characterization of Caenorhabditis elegans TRX-3, the first metazoan thioredoxin with an intestine-specific expression pattern. By using green fluorescent protein reporters we have found that TRX-3 is expressed in both the cytoplasm and the nucleus of intestinal cells, with a prominent localization at the apical membrane. Although intestinal function, reproductive capacity, longevity, and resistance of trx-3 loss-of-function mutants to many stresses are indistinguishable from those of wild-type animals, we have observed a slight reduction in size and a minor reduction in the defecation cycle timing of trx-3 mutants. Interestingly, trx-3 is induced upon infection by Photorhabdus luminescens and Candida albicans, and TRX-3 overexpression provides a modest protection against these pathogens. Together, our data indicate that TRX-3 function in the intestine is dispensable for C. elegans development but may be important to fight specific bacterial and fungal infections.